RATIFIKASI THE INTERNATIONAL CONVENTION ON THE ELIMINATION OF ALL FORMS OF RACIAL DISCRIMINATION (ICERD) OLEH SINGAPURA TAHUN 2017 - Salby Aurizaldi Putri; Yessi Olivia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
This research describes about Singapore’s reason for ratified International Convention on the Elimination of All Forms of Racial Discrimination (ICERD) in 2017. Singapore as a multiracial state is upholding social harmony, yet that does not make Singapore free from racial discrimination. Minority and immigrant worker often get discrimination. The government has made attempts to reduce racial discrimination in its society. As a country that adheres to semi-authoritarian system, many individual rights are limited by the government, as well as civil society groups whose movements are limited by strict regulations and policies. However, in contrast to the facts, Singapore ratified ICERD in 2017. The author collects data from books, academic journals, official websites, articles and also official documents related to this research, then uses document analysis as a research method. The issue of this study is to analyze Singapore’s reason which has ratified ICERD in 2017 using theory the cost of commitment from Oona Hathaway, and the level of analysis is state. The result of the study shows that civil society groups played a very large role in the government’s decision to ratify ICERD in 2017. One of the civil society group coalition, COSINGO, succeeded in submitting their reports to UPR through the UPR Pre-Session and recommended Singapore to ratify ICERD as soon as possible. Many actions were taken by civil society groups which indirectly influenced the government to ratify ICERD in 2017. Keywords: ICERD, Civil Society Groups, Racial Discrimination, Ratification.